Organic Pollutants - Walker, C. (CRC Press, 2009)
Significantly updated, revised, and expanded, this third edition presents the basic principles of ecotoxicology along with the major organic pollutants. Two new chapters cover endocrine disruptors and neurotoxicity and its behavioral effects. The text also provides additional information on biomarker approaches and offers an overview of new technologies, such as microarray assays, that are being developed to address complex pollution problems. Through a mechanistic approach, this book continues to provide essential knowledge of toxic mechanisms that produce adverse ecological effects, serving as valuable guidance for carrying out the risk assessment of environmental chemicals.